Electric metre. (Economist, 1995)
Perl, a computer language developed by Larry Wall to cut across the barriers between different versions of the UNIX operating system, is enjoying reincarnation in 1995 with the release of version 5. Perl is a practical language that provides standard ways of dealing with the two most common tasks facing system managers: file handling and process control—the job of monitoring what programs the operating system is running. Its numerous charms and ease of use have made Perl very successful. The advantages of Perl are described.